INTEGRATION OF GREEN EDUCATION IN THE LEARNING PROCESS IN FACING NATIONAL AND GLOBAL ISSUES - Nada Nabilah; Cici Puspaningrum (RADJA PUBLIKA, 2024)
This research explains about Green Education in the learning process in Facing National and Global Issues. The method used in this research is qualitative descriptive analysis at SMA Negeri 1 Tebing Tinggi Kab. Serdang Bedagai. The data collection techniques were carried out by means of field observations and interviews. The results of this research show that globalization has a major impact on life and the environment. The existence of extreme climate change, food crises and ongoing economic difficulties are examples of sustainability issues that must be faced in today's global world. Considering the importance of the environment for human life, it is necessary to take responsibility for the sustainability of the environment for future generations. Schools have access to integrating green education values ​​through the application of Education for Sustainable Development (ESD) development methods such as critical thinking skills and attitude skills in making decisions regarding issues relating to environmental quality both nationally and globally.